Asphalt-based carbon material, preparation and application thereof, sodium-ion battery negative electrode material, sodium-ion battery negative electrode and application

By using amorphous carbon materials prepared by asphalt raw materials and potassium salts, the problems of petroleum-based carbon materials in sodium ion batteries are solved, and efficient sodium ion battery performance and low-cost production are achieved.

CN119569021AActive Publication Date: 2025-03-07CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311147135.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-07
Estimated Expiration
2043-09-06

AI Technical Summary

Technical Problem

The existing petroleum-based carbon materials have problems such as low specific capacity and high sodium storage voltage in sodium ion batteries, which limits their commercial applications.

Method used

Using asphalt raw materials as carbon source and potassium salt as pore-making activator, amorphous carbon materials with similar structures and properties to hard carbon are prepared by sand grinding and spray drying.

Benefits of technology

The prepared asphalt-based carbon material exhibits high reversible capacity and first-week Coulomb efficiency in sodium ion batteries, and has low raw material costs, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569021A_ABST
    Figure CN119569021A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemistry, and discloses an asphalt-based carbon material, preparation and application thereof, a sodium-ion battery negative electrode material, a sodium-ion battery negative electrode and application, and the method comprises the following steps: (1) mixing asphalt powder, potassium salt and a solvent to obtain mixed slurry; (2) carrying out drying treatment and high-temperature calcination on the mixed slurry; wherein the mass ratio of the asphalt powder to the potassium salt in the step (1) is (1-3): 1. According to the method, the raw materials are easy to obtain, industrial amplification is easy, and the prepared asphalt-based carbon material is applied to a sodium ion battery and has high reversible capacity and first-week coulombic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to a pitch-based carbon material and its preparation and application, as well as a sodium ion battery negative electrode material and a sodium ion battery negative electrode and its application. Background Art

[0002] The existing secondary battery systems mainly include nickel-metal hydride batteries, lead-acid batteries, lithium-ion batteries and polymer lithium-ion batteries. Among them, lithium-ion batteries have the advantages of high energy density, good cycle stability and low self-discharge, and have been widely used in mobile electronics, communication equipment, electric devices and electric vehicles. However, lithium-ion batteries still face the problem of lithium resource shortage. Therefore, the development of new high-energy-density secondary batteries to cope with resource shortages is a research focus in this field. The application of sodium-ion batteries can not only alleviate the global lithium resource shortage and narrow the gap between supply and demand; on the other hand, the abundant sodium salt reserves and mature extraction processes jointly determine the lower material cost and cost fluctuation range of sodium-ion batteries.

[0003] However, the promotion and application of sodium-ion batteries also face certain problems. Similar to the working principle of lithium-ion batteries, the design and development of electrode materials that can accommodate the stable insertion and extraction of sodium ions is the key to the commercialization of sodium-ion batteries. In academia, a variety of sodium-ion battery negative electrode materials have been developed, including conversion reaction materials, alloying materials, titanium-based materials and carbon-based materials. Carbon-based materials are rich in variety and wide in source. Amorphous carbon-based negative electrodes (including hard carbon and soft carbon) show high reversible specific capacity and good cycle performance in sodium-ion batteries. Since their discovery, researchers have conducted a lot of exploration and research on this type of material. Hard carbon materials have become the most promising negative electrode materials for sodium-ion secondary batteries due to their high specific capacity and low sodium storage voltage. However, the carbon yield of the precursor for producing hard carbon is currently low, resulting in high cost of hard carbon materials, which restricts its commercial application. The preparation of carbon-based negative electrode materials with petroleum-based products not only has high carbon yield and low cost, but also has a complete raw material supply chain and is easy to quickly integrate into the market. However, the soft carbon materials obtained by direct high-temperature carbonization of materials such as petroleum coke and asphalt have problems such as low specific capacity and high sodium storage voltage. Porous structure design is generally considered to be a reliable strategy to improve the ion transport capacity of Na-ion batteries and increase the number of active sites for sodium storage.

[0004] Therefore, how to obtain carbon-based materials with high specific capacity and low sodium storage voltage by constructing a suitable pore structure is the technical key. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of low specific capacity and high sodium storage voltage of petroleum-based carbon materials in the prior art, and to provide asphalt-based carbon materials and their preparation and application, as well as sodium ion battery negative electrode materials and sodium ion battery negative electrodes and applications. The method uses asphalt raw materials as carbon sources, and composites asphalt powder with activator potassium salt, and uses sand milling and spray drying technology to prepare amorphous carbon materials with similar structures and properties to hard carbon, which is easy to scale up industrially. The prepared asphalt-based carbon materials are applied to sodium ion batteries, which have high reversible capacity and first-cycle coulomb efficiency.

[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a pitch-based carbon material, wherein the method comprises the following steps:

[0007] (1) mixing asphalt powder, potassium salt and a solvent to obtain a mixed slurry;

[0008] (2) drying and calcining the mixed slurry at high temperature;

[0009] Wherein, the mass ratio of the asphalt powder and potassium salt in step (1) is (1-3):1.

[0010] The second aspect of the present invention provides a pitch-based carbon material obtained by the preparation method described in the first aspect.

[0011] The third aspect of the present invention provides an application of the asphalt-based carbon material described in the second aspect in a sodium ion battery.

[0012] The fourth aspect of the present invention provides a negative electrode material for a sodium ion battery, wherein the negative electrode material comprises the asphalt-based carbon material described in the second aspect and a binder.

[0013] A fifth aspect of the present invention provides a sodium ion battery negative electrode, the negative electrode comprising a current collector and a negative electrode material coated and / or filled on the current collector, the negative electrode material being the negative electrode material described in the fourth aspect of the present invention.

[0014] The sixth aspect of the present invention provides the use of the sodium ion battery negative electrode described in the fifth aspect in a sodium ion battery.

[0015] Through the above technical solution, the beneficial effects obtained are as follows:

[0016] (1) In the present invention, asphalt raw material is used as a carbon source, potassium salt is introduced as a pore-forming activator, and an amorphous carbon material having a structure and properties similar to hard carbon is prepared. The prepared asphalt-based carbon material is applied to sodium ion batteries and has high reversible capacity and first-cycle coulombic efficiency;

[0017] (2) In the present invention, the cost of asphalt raw materials is low, the introduced potassium salt can be recovered and reused, the cost of raw materials is low, and the sand milling and spray drying technologies are used, which is easy to scale up industrially and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is the XRD spectrum of the pitch-based carbon material prepared in Example 1;

[0019] Figure 2 This is the SEM image of the pitch-based carbon material prepared in Example 1. DETAILED DESCRIPTION

[0020] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0021] A first aspect of the present invention provides a method for preparing a pitch-based carbon material, wherein the method comprises the following steps:

[0022] (1) mixing asphalt powder, potassium salt and a solvent to obtain a mixed slurry;

[0023] (2) drying and calcining the mixed slurry at high temperature;

[0024] Wherein, the mass ratio of the asphalt powder and potassium salt in step (1) is (1-3):1.

[0025] In the present invention, asphalt raw material is used as a carbon source, potassium salt is introduced as a pore-forming activator, and an amorphous carbon material having a structure and properties similar to hard carbon is prepared, which is used as a negative electrode active material in sodium ion batteries and has high reversible capacity and first-cycle coulombic efficiency.

[0026] In the present invention, the "asphalt" has the conventional definition in the art, and may be petroleum asphalt and / or coal asphalt.

[0027] According to the present invention, preferably, the mass ratio of the asphalt powder and potassium salt in step (1) is (1-3):1, such as 1:1, 1.25:1, 1.5:1, 1.75:1, 2:1, 2.25:1, 2.5:1, 3:1, or any range between the two, preferably (1.5-2.5):1. The asphalt powder and potassium salt are mixed according to the above ratio, and the potassium salt is compounded with the asphalt raw material as a pore-forming activator to prepare an asphalt-based carbon material with high reversible capacity and first-cycle coulomb efficiency. If the amount of potassium salt added is too much, the first coulomb efficiency is reduced; if the amount added is too little, the activation effect is limited.

[0028] According to the present invention, the average particle size of the asphalt powder is not particularly limited, and it can be a powder with uniform particle size distribution. Preferably, the average particle size of the asphalt powder is 5-15 microns, preferably 8-12 microns. Asphalt powder with an average particle size not within the above range can be obtained by grinding and sieving to obtain asphalt powder with an average particle size satisfying the above range, and the grinding and sieving methods are conventional methods in the art. The average particle size of the asphalt powder is measured by a laser particle size analyzer.

[0029] According to the present invention, preferably, the softening point of the asphalt powder is 100-300° C., preferably 200-300° C. In the present invention, the method for testing the softening point of the asphalt is to place the asphalt raw material in a special test tube, heat it at a stable heating rate under a nitrogen atmosphere, and continuously pierce the asphalt with a steel needle rod with a diameter of 1 mm during the process. When the asphalt becomes soft and begins to stick to the steel needle, the temperature at this time is recorded, which is the softening point of the asphalt.

[0030] According to the present invention, preferably, the mass percentage of ash in the asphalt powder is 0-0.5wt%, preferably 0-0.1wt%. In the present invention, ash has the conventional interpretation in the art, and refers to the inorganic matter remaining after the asphalt is burned or calcined. In the present invention, the mass percentage of ash in the asphalt powder is measured by a roasting method: (1) Record the initial mass of the asphalt sample; (2) Place the asphalt sample in a drying oven and dry it to constant weight at a constant temperature of 110°C-115°C; (3) Take out the sample, put it in a roaster, first bake it at a low temperature for 30 minutes, and then raise it to 815°C and bake it to constant weight; (4) Take out the sample, put it in an air cooler to cool it, and weigh the sample. The mass difference is the ash content, and the ratio of the ash content to the mass of the asphalt sample is recorded as the mass percentage of ash.

[0031] In the present invention, asphalt powder whose softening point and ash content meet the above conditions is used to prepare asphalt-based carbon material. The asphalt has a high softening point and a low ash content, which is beneficial to improving the carbon yield and the selection of the pretreatment process.

[0032] In the present invention, the source of the asphalt powder is not particularly limited, and it can be commercially available or prepared by existing methods, as long as the asphalt powder meets the above conditions.

[0033] According to the present invention, the type of the potassium salt is not particularly limited, and is a conventional potassium salt in the art. Preferably, the potassium salt is selected from at least one of potassium hydroxide, potassium carbonate and potassium bicarbonate, preferably potassium hydroxide and / or potassium bicarbonate. In the present invention, the potassium salt can be recycled and reused by subsequent washing, thereby achieving environmental protection and reducing costs.

[0034] According to the present invention, there is no particular limitation on the type of the solvent, and those skilled in the art may select conventional volatile organic solvents and / or inorganic solvents in the art, as long as the asphalt powder and potassium salt can be mixed evenly and can be volatilized and removed. Preferably, the solvent is ethanol and / or water. The above solvent is added to prepare a mixed slurry, and in the subsequent sand milling process, the asphalt powder and potassium salt can be mixed more evenly.

[0035] According to the present invention, the amount of the solvent added is not particularly limited. According to a preferred embodiment of the present invention, the total mass ratio of the solvent to the asphalt powder and the potassium salt is 2-30:1, for example, 2:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, or any range between the two, preferably 5-15:1.

[0036] According to the present invention, preferably, step (1) further comprises sand grinding the mixed slurry, and the sand grinding conditions include:

[0037] The sand milling time is 2-12 hours, preferably 3-8 hours; the sand milling speed is 1500-2500 r / min, preferably 1800-2200 r / min. In the present invention, the sand milling equipment is not particularly limited, and it only needs to be able to sand mill the mixed slurry evenly. Those skilled in the art can select conventional sand milling equipment.

[0038] According to the present invention, preferably, in step (2), the drying treatment conditions include: spray drying under a protective atmosphere, a spray pressure of 0.1-0.4MPa, preferably 0.2-0.3MPa, and a temperature of 100-220°C, preferably 150-200°C. In the present invention, preferably, spray drying is used to treat the mixed slurry under the above conditions, which can volatilize the solvent while ensuring the morphology of the mixed material, not easily forming agglomerates, good dispersibility, and ensuring the cyclic stability of the obtained asphalt-based carbon material.

[0039] In the present invention, the type of the protective atmosphere is not particularly limited, and those skilled in the art may select a conventional protective atmosphere with stable properties, preferably at least one selected from nitrogen, helium, argon and neon.

[0040] According to the present invention, preferably, the conditions for high temperature calcination include: under a protective atmosphere, the reaction temperature is 1000-1500°C, preferably 1200-1400°C, the heating rate is 2-10°C / min, preferably 3-8°C / min, and the reaction time is 0.5-4 hours, preferably 1-3 hours.

[0041] In the present invention, the equipment used for the spray drying and high-temperature calcination is not particularly limited, and those skilled in the art can select them adaptively. According to a specific embodiment of the present invention, the high-temperature calcination is carried out in a tubular furnace.

[0042] In the present invention, preferably, the product is naturally cooled after high-temperature calcination, which helps to obtain a stable pitch-based carbon material and avoids the danger of operating the equipment used for calcination at high temperature.

[0043] According to the present invention, preferably, the method further comprises crushing, washing and drying the product of high temperature calcination. In the present invention, there is no particular limitation on the conditions of crushing, washing and drying, and those skilled in the art can adjust them adaptively. According to a preferred embodiment of the present invention, the product of high temperature calcination is washed to neutrality with deionized water. The product of high temperature calcination can be washed to remove potassium salt in the product, and the solution obtained by washing can be concentrated and dried to recover the potassium salt added in step (1), thereby realizing the reuse of potassium salt.

[0044] The second aspect of the present invention provides a pitch-based carbon material obtained by the preparation method described in the first aspect.

[0045] According to the present invention, preferably, the interlayer spacing of the pitch-based carbon material is 0.36-0.4 nm, preferably 0.36-0.38 nm. This preferred embodiment is more conducive to improving the sodium storage capacity of the pitch-based carbon material. The interlayer spacing is the carbon interlayer spacing of the pitch-based carbon material, which is calculated by the Bragg equation.

[0046] Specifically, in the present invention, the XRD diffractometer used for the X-ray diffraction spectrum of the pitch-based carbon material is an XRD-6000 X-ray powder diffractometer (Shimadzu, Japan), and the XRD test conditions are: Cu target, Kα ray (wavelength λ = 0.154nm), tube voltage of 40kV, tube current of 200mA, and scanning speed of 10° (2θ) / min. Figure 1The X-ray diffraction spectrum of the pitch-based carbon material has a diffraction peak at a 2θ angle of 22.3±0.5°, which corresponds to the (002) diffraction peak of the hard carbon material, proving that a hard carbon material is generated in the pitch-based carbon material.

[0047] The third aspect of the present invention provides an application of the asphalt-based carbon material described in the second aspect in a sodium ion battery.

[0048] According to the present invention, preferably, the pitch-based carbon material is used in a negative electrode material for a sodium ion battery.

[0049] The fourth aspect of the present invention provides a negative electrode material for a sodium ion battery, wherein the negative electrode material comprises the asphalt-based carbon material described in the second aspect and a binder.

[0050] In the present invention, the negative electrode material prepared by using the above pitch-based carbon material is used in a sodium ion battery and has a high reversible capacity and first-cycle coulombic efficiency.

[0051] In the present invention, the amount and type of the binder for the electrode material can be selected in a wide range and can be selected according to conventional technical means in the art. According to a preferred embodiment of the present invention, the binder is sodium alginate, which can be provided in the form of an aqueous solution thereof. The amount of the binder can be such that the asphalt-based carbon material is prepared into a negative electrode material through the binder, and those skilled in the art can adjust it adaptively.

[0052] A fifth aspect of the present invention provides a sodium ion battery negative electrode, the negative electrode comprising a current collector and a negative electrode material coated and / or filled on the current collector, the negative electrode material being the negative electrode material described in the fourth aspect of the present invention.

[0053] The sixth aspect of the present invention provides the use of the sodium ion battery negative electrode described in the fifth aspect in a sodium ion battery.

[0054] According to the present invention, preferably, the sodium ion battery comprises an electrode group and a non-aqueous electrolyte, wherein the electrode group and the non-aqueous electrolyte are sealed in a battery casing, the electrode group comprises a positive electrode, a negative electrode and a diaphragm, the diaphragm is located between the positive electrode and the negative electrode, and the negative electrode is the negative electrode of the sodium ion battery described in the fifth aspect.

[0055] In the present invention, the non-aqueous electrolyte refers to an electrolyte solution whose solvent is not water. Those skilled in the art can select a suitable non-aqueous electrolyte according to the composition of the sodium ion battery, and no limitation is made here.

[0056] According to a particularly preferred embodiment of the present invention, a method for preparing a pitch-based carbon material comprises the following steps:

[0057] (1) mixing asphalt powder, potassium salt and a solvent to obtain a mixed slurry;

[0058] (2) spray drying the mixed slurry and calcining it at high temperature;

[0059] Wherein, the mass ratio of the asphalt powder and potassium salt in step (1) is (1.5-2.5):1;

[0060] The softening point of the asphalt powder is 200-300°C;

[0061] The mass percentage of ash in the asphalt powder is 0-0.1wt%;

[0062] The potassium salt is selected from at least one of potassium hydroxide, potassium carbonate and potassium bicarbonate

[0063] The total mass ratio of the solvent to the asphalt powder and the potassium salt is 5-15:1.

[0064] The present invention will be described in detail below through examples and comparative examples. In the following examples and comparative examples, the room temperature is 25°C; unless otherwise specified, all reagents used are commercially available;

[0065] The microstructure of pitch-based carbon materials was observed by scanning electron microscopy.

[0066] Example 1

[0067] (1) crushing and sieving asphalt (high-temperature petroleum asphalt, the softening point of asphalt is 278°C, and the ash content is 0.05wt%) to obtain asphalt powder with an average particle size of 10 μm, mixing the asphalt powder and KOH in a mass ratio of 2:1, dissolving in ethanol solvent, the mass ratio of ethanol solvent to asphalt powder and KOH is 10:1, and sand milling for 6 hours at a sand milling speed of 2200 r / min;

[0068] (2) spray drying the mixed slurry obtained in step (1) under a nitrogen atmosphere at a spray pressure of 0.2 MPa and a temperature of 180° C.;

[0069] The spray-dried product was placed in a tube furnace, heated to 1300°C at a heating rate of 5°C / min under a nitrogen atmosphere, kept at this temperature for 2 hours, and then cooled naturally;

[0070] (3) The material obtained in step (2) is crushed, washed with deionized water until neutral, and finally dried to obtain a pitch-based carbon material.

[0071] Figure 1 is the X-ray diffraction (XRD) pattern of the prepared pitch-based carbon material. Figure 1 It can be seen that there is a broadened (002) diffraction peak at a 2θ angle of 24.0°, indicating that it has a high degree of amorphism and a large interlayer spacing, showing the characteristics of hard carbon.

[0072] Figure 2 The SEM image of the prepared pitch-based carbon material is Figure 2 It can be seen that the original lamellar structure of the asphalt is destroyed after the alkali activation treatment, and the surface of the sample becomes rough with obvious holes.

[0073] Example 2

[0074] (1) crushing and sieving asphalt (high-temperature petroleum asphalt, the softening point of asphalt is 278°C, and the ash content is 0.05wt%) to obtain asphalt powder with an average particle size of 10 μm, mixing the asphalt powder and KOH in a mass ratio of 1:1, dissolving in ethanol solvent, the mass ratio of ethanol solvent to asphalt powder and KOH is 10:1, and sand milling for 6 hours at a sand milling speed of 2200 r / min;

[0075] (2) spray drying the mixed slurry obtained in step (1) under a nitrogen atmosphere at a spray pressure of 0.2 MPa and a temperature of 180° C.;

[0076] The spray-dried product was placed in a tube furnace, heated to 1300°C at a heating rate of 5°C / min under a nitrogen atmosphere, kept at this temperature for 2 hours, and then cooled naturally;

[0077] (3) The material obtained in step (2) is crushed, washed with deionized water until neutral, and finally dried to obtain a pitch-based carbon material.

[0078] Example 3

[0079] (1) Asphalt (high-temperature petroleum asphalt, the softening point of asphalt is 278°C, and the ash content is 0.05wt%) is crushed and sieved to obtain asphalt powder with an average particle size of 10 μm, the asphalt powder and KOH are mixed in a mass ratio of 3:1, dissolved in ethanol solvent, the mass ratio of ethanol solvent to asphalt powder and KOH is 10:1, and sand milled for 6 hours at a sand milling speed of 2200 r / min;

[0080] (2) spray drying the mixed slurry obtained in step (1) under a nitrogen atmosphere at a spray pressure of 0.2 MPa and a temperature of 180° C.;

[0081] The spray-dried product was placed in a tube furnace, heated to 1300°C at a heating rate of 5°C / min under a nitrogen atmosphere, kept at this temperature for 2 hours, and then cooled naturally;

[0082] (3) The material obtained in step (2) is crushed, washed with deionized water until neutral, and finally dried to obtain a pitch-based carbon material.

[0083] Example 4

[0084] (1) crushing and sieving asphalt (high-temperature petroleum asphalt, the softening point of asphalt is 278°C, and the ash content is 0.05wt%) to obtain asphalt powder with an average particle size of 10 μm, mixing the asphalt powder and potassium carbonate in a ratio of 2:1, dissolving the mixture in an ethanol solvent, wherein the mass ratio of the ethanol solvent to the asphalt powder and potassium carbonate is 10:1, and sand milling for 6 hours at a sand milling speed of 2200 r / min;

[0085] (2) spray drying the mixed slurry obtained in step (1) under a nitrogen atmosphere at a spray pressure of 0.2 MPa and a temperature of 180° C.;

[0086] The spray-dried product was placed in a tube furnace, heated to 1300°C at a heating rate of 5°C / min under a nitrogen atmosphere, kept at this temperature for 2 hours, and then cooled naturally;

[0087] (3) The material obtained in step (2) is crushed, then washed with deionized water until it is neutral, and finally dried to obtain a pitch-based carbon material.

[0088] Example 5

[0089] The method of Example 1 is followed, except that the softening point of the asphalt powder is 200° C., the ash content is 0.2 wt %, and the other conditions are the same as those of Example 1, to obtain a asphalt-based carbon material.

[0090] Example 6

[0091] The method of Example 1 is followed, except that in step (2), the spray-dried product is placed in a tubular furnace, heated to 1500°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept warm for 2 hours, and then cooled naturally. Other conditions are the same as in Example 1, to obtain a pitch-based carbon material.

[0092] Example 7

[0093] The method of Example 1 is followed, except that step (2) is dried by oven drying at a temperature of 180° C. to obtain a pitch-based carbon material.

[0094] Comparative Example 1

[0095] (1) crushing and sieving asphalt (high-temperature petroleum asphalt, the softening point of asphalt is 278° C., and the ash content is 0.05 wt %) to obtain asphalt powder with an average particle size of 10 μm, mixing the asphalt powder and KOH in a ratio of 2:1, placing the mixed powder in a ball mill, and dry grinding for 6 hours;

[0096] (2) placing the product obtained in step (1) in a tube furnace, heating the temperature to 1300° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, keeping the temperature for 2 hours, and then cooling naturally;

[0097] (3) The material obtained in step (1) is crushed, washed with deionized water until neutral, and finally dried to obtain a pitch-based carbon material.

[0098] Comparative Example 2

[0099] (1) crushing and sieving asphalt (high-temperature petroleum asphalt, the softening point of asphalt is 278° C., and the ash content is 0.05 wt %) to obtain asphalt powder with an average particle size of 10 μm;

[0100] (2) The asphalt powder was placed in a tubular furnace, and under a nitrogen atmosphere, the temperature was increased to 1300°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, and then the temperature was naturally cooled to obtain a asphalt-based carbon material.

[0101] Test Case

[0102] The asphalt-based carbon materials prepared in the examples and comparative examples were prepared into negative electrode sheets for sodium ion batteries and assembled into batteries.

[0103] 1) Preparation of negative electrode sheet:

[0104] The dried asphalt-based carbon materials obtained in the above embodiments and comparative examples were mixed with an aqueous solution of sodium alginate (binder, the mass fraction of sodium alginate was 2%) in a mass ratio of 9:1, and stirred on a magnetic stirrer for 6 hours to obtain a paste slurry; the obtained paste slurry was evenly coated on the current collector copper foil, and then dried in a vacuum drying oven at 100°C for 20 hours for use.

[0105] 2) Battery assembly:

[0106] The dried negative electrode was made into a circular electrode with a diameter of 12 mm; and maintained at a pressure of 8 MPa for 30-180 seconds to obtain the negative electrode of the sodium ion battery. The metal sodium sheet was used as the counter electrode, the glass fiber was used as the diaphragm, 1 mol / L sodium hexafluorophosphate was selected as the electrolyte, and the solvent volume ratio EC (ethylene carbonate): DEC (diethyl carbonate) = 1:1 was assembled into a CR2032 button cell. The entire battery assembly was completed in a glove box to prepare a sodium ion battery.

[0107] Routine battery performance test: The battery was charged and discharged using the LAND CT2001A charge and discharge instrument from Wuhan Rambo Electronics Co., Ltd. The charge and discharge voltage range was 0V to 2.5V, and the specific capacity of the assembled sodium-ion battery was tested at a rate of 0.1C.

[0108] The performance test results of the sodium ion batteries prepared in the examples and comparative examples are shown in Table 1.

[0109] Table 1

[0110]

[0111]

[0112] It can be seen from the results in Table 1 that the present invention uses low-cost asphalt and potassium salt as precursor carbon sources to prepare hard carbon materials, which are used as asphalt-based carbon materials for sodium ion batteries in sodium ion batteries, and have high reversible capacity and first-week coulombic efficiency.

[0113] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a pitch-based carbon material, characterized in that: The method comprises the following steps: (1) mixing asphalt powder, potassium salt and a solvent to obtain a mixed slurry; (2) drying and calcining the mixed slurry at high temperature; Wherein, the mass ratio of the asphalt powder and potassium salt in step (1) is (1-3):

1.

2. The preparation method according to claim 1, wherein The mass ratio of the asphalt powder and potassium salt in step (1) is (1.5-2.5):1; Preferably, the average particle size of the asphalt powder is 5-15 microns, preferably 8-12 microns; Preferably, the softening point of the asphalt powder is 100-300°C, preferably 200-300°C; Preferably, the mass percentage of ash in the asphalt powder is 0-0.5wt%, preferably 0-0.1wt%.

3. The preparation method according to claim 1 or 2, wherein The potassium salt is selected from at least one of potassium hydroxide, potassium carbonate and potassium bicarbonate; Preferably, the solvent is ethanol and / or water; Preferably, the total mass ratio of the solvent to the asphalt powder and the potassium salt is 2-30:1, preferably 5-15:

1.

4. The preparation method according to any one of claims 1 to 3, wherein In step (2), the drying treatment conditions include: spray drying under a protective atmosphere, the spray pressure is 0.1-0.4 MPa, preferably 0.2-0.3 MPa, and the temperature is 100-220° C., preferably 150-200° C.; Preferably, the conditions for high temperature calcination include: under a protective atmosphere, the reaction temperature is 1000-1500°C, preferably 1200-1400°C, the heating rate is 2-10°C / min, preferably 3-8°C / min, and the reaction time is 0.5-4 hours, preferably 1-3 hours; Preferably, the protective atmosphere is selected from at least one of nitrogen, helium, argon and neon.

5. The preparation method according to any one of claims 1 to 4, wherein: Step (1) further comprises sand grinding the mixed slurry, wherein the sand grinding conditions include: The sanding time is 2-12 hours, preferably 3-8 hours; the sanding speed is 1500-2500 r / min, preferably 1800-2200 r / min.

6. The preparation method according to any one of claims 1 to 5, wherein: The method further comprises pulverizing, washing and drying the high-temperature calcined product.

7. A pitch-based carbon material obtained by the preparation method according to any one of claims 1 to 6; Preferably, the interlayer spacing of the pitch-based carbon material is 0.36-0.4 nm, preferably 0.36-0.38 nm.

8. Use of the pitch-based carbon material according to claim 7 in sodium ion batteries; Preferably, the asphalt-based carbon material is used in a negative electrode material for a sodium ion battery.

9. A negative electrode material for a sodium ion battery, comprising the pitch-based carbon material according to claim 7 and a binder.

10. A sodium ion battery negative electrode, characterized in that: The negative electrode comprises a current collector and a negative electrode material coated and / or filled on the current collector, and the negative electrode material is the negative electrode material according to claim 9.

11. Use of the sodium ion battery negative electrode according to claim 10 in a sodium ion battery; Preferably, the sodium ion battery comprises an electrode group and a non-aqueous electrolyte, wherein the electrode group and the non-aqueous electrolyte are sealed in a battery housing, and the electrode group comprises a positive electrode, a negative electrode and a separator, wherein the separator is located between the positive electrode and the negative electrode.

Citation Information

Patent Citations

  • Asphalt hard carbon material, and preparation method and application thereof

    CN105645379A

  • Preparation method of mesopore-rich asphalt-based super activated carbon

    CN107188172A

  • Carboxyl asphaltic base porous carbon and preparation method and application thereof

    CN108455604A

  • Pitch-based porous carbon material and preparation method thereof, silicon-carbon negative electrode material and secondary battery

    CN109065861A

  • Preparation method and application of high-purity medium-temperature coal pitch based super active carbon

    CN109133055A

Cited By

  • Rock asphalt-based porous carbon spherical particles and preparation method thereof

    CN120117606A